ELTV Channel 6 News (African Knowledges and the History Publication since the 1970s)
News on various topics, including heavy rains, infrastructure and traffic issues in Monrovia; President Samuel Kanyon Doe's visit at National Trust Company; and International Cooperation Day.
Keywords: News; Public Affairs